Enhancing sustainable performance among Islamic banks in Saudi Arabia: the role of management support and environmental innovation - Ibrahim Abiodun Oladapo (Cogent Social Sciences, 2024)
The global banking industry faces increasing pressure to address its contribution to environmental challenges, including rising greenhouse gas emissions and climate change. There is a notable research gap in how innovative approaches, especially environmental innovation and strategic management, can address these challenges within the banking sector. This paper aims to bridge the lacuna by exploring how management support and environmental innovation influence sustainable environmental performance within the banking sector, specifically focusing on Islamic banks in Saudi Arabia. In this paper, a theoretical framework grounded in resource‑based view and stakeholder theories was adopted to guide the research. Using data collected from 203 banking professionals via convenience random sampling, the study reveals management support is significant and positively related to both environmental innovation (β = 0.749) and environmental performance (β = 0.563). Furthermore, increased investment in green technologies, the implementation of environmental management systems, and ethical practices contribute significantly to enhanced environmental performance (β = 0.252). The analysis also shows that management support exerts an indirect effect on environmental performance through environmental innovation (β = 0.189), emphasizing the importance of a stronger culture of sustainability within the organization. This research offers recommendations for banks and regulators to promote sustainable banking practices, highlighting its potential benefits for brand reputation, productivity, and overall effectiveness.